Preliminary report on the 2012 and 2013 excavation seasons at Jiyeh(Porphyreon): work in sector D (residential Quarter) - Tomasz Waliszewski; Magdalena Antos; Piotr Jaworski; Piotr Makowski; Marcin Romaniuk; Rafał Solecki; Agnieszka Szymczak (Polish Archaeology in the Mediterranean, 2016)
Archeological work in the 2012 and 2013 seasons in Jiyeh (Porphyreon), which lies onthe Phoenician coast north of ancient Sidon, was focused on reconstructing the history of settlementon the site. At least three phases were identified and dated to the Iron Age II, the Persian–Hellenistic–Roman period and late antiquity. The early dating of the functioning of the Christianbasilica to the 4th–5th century AD was also confirmed in trial pits. The complex and unusualsewage installation discharging rainwater from the roofs and streets of the 5th-century settlementcontributed important data for studies of late antique domestic architecture in the region.